Editorial (Inglês) - Mota, Mauricio (Revista de Direito da Cidade, 2019)
The Journal of City Law a journal ranked by MEC / CAPES as Qualis A1, Law and registered in the Web of Science, is pleased to inform all its readers that it has been indexed in the library of the EBS Universität für Wirtschaft und Recht, Germany’s most traditional private Business University, which combines scientifically solid training with innovative concepts, forming generations of highly skilled business professionals. In our Section Essays we publish four (4) unpublished essays, two on public policies: "The popular participation in the municipal public management from the municipal councils of social welfare" and "Controversies in a lawsuit of usucapião of urban area: Reflections from of a process of Caxias do Sul - RS". In this issue of the Journal we have kept our staff of our reviewers / evaluators, from countless states in the country and also from many foreign countries, in a total of more than 410 evaluators. We thank, as always, all the readers, authors, evaluators and collaborators for the collaboration and trust and for the always excellent work done. We always remember that the submissions for the Journal Of City Law are permanent and must be carried out by the system, directly on the Journal’s page. Good Reading to all!